Effects of Estradiol on Immunoglobulin G Glycosylation: Mapping of the Downstream Signaling Mechanism - Mijakovac, Anika; Jurić, Julija; Kohrt, Wendy M.; Krištić, Jasminka; Kifer, Domagoj; Gavin, Kathleen M.; Miškec, Karlo; Frkatović, Azra; Vučković, Frano; Pezer, Marija; Vojta, Aleksandar; Nigrović, Peter A.; et al. (Frontiers in Immunology, 2021)
Glycans attached to immunoglobulin G (IgG) directly affect this antibody effector functions and regulate inflammation at several levels. The composition of IgG glycome changes significantly with age. In women, the most notable change coincides with the perimenopausal period. Aiming to investigate the effect of estrogen on IgG glycosylation, we analysed IgG and total serum glycomes in 36 healthy premenopausal women enrolled in a randomized controlled trial of the gonadotropin-releasing hormone analogue (GnRHAG) leuprolide acetate to lower gonadal steroids to postmenopausal levels and then randomized to transdermal placebo or estradiol (E2) patch. The suppression of gonadal hormones induced significant changes in the IgG glycome, while E2 supplementation was sufficient to prevent changes. The observed glycan changes suggest that depletion of E2 primarily affects B cell glycosylation, while liver glycosylation stays mostly unchanged. To determine whether previously identified IgG GWAS hits RUNX1, RUNX3, SPINK4, and ELL2 are involved in downstream signalling mechanisms, linking E2 with IgG glycosylation, we used the FreeStyle 293-F transient system expressing IgG antibodies with stably integrated CRISPR/dCas9 expression cassettes for gene up- and downregulation. RUNX3 and SPINK4 upregulation using dCas9-VPR resulted in a decreased IgG galactosylation and, in the case of RUNX3, a concomitant increase in IgG agalactosylation.